Automating hospital ICU emergency signaling - Zahan, Fahmida; Mahmud, Nusrat; Nawshin, Amanna; Ahmed, Ferdousi (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.